2016
DOI: 10.1021/acs.cgd.6b01470
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Crystallization Inhibition Properties of Bile Salts

Abstract: Bile salts are natural surfactants present in the human gastrointestinal tract. Therefore, it is essential to consider their effect on the dissolution and crystallization tendency of oral drug formulations. Although a recent study showed that sodium taurocholate delayed nucleation for 11 structurally diverse compounds, there is limited information about the crystallization inhibition properties of other bile salts and whether they are interchangeable in this context. In this study, we evaluated the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 61 publications
(103 reference statements)
4
54
1
Order By: Relevance
“…The significant difference between telaprevir induction times in FaSSIF and in the mixed micelles with lecithin solutions further demonstrates that STC may not be a good surrogate for human bile composition. Our results are in general agreement with those of Li et al 12 who reported a two fold increase in celecoxib induction time in mixed bile salt solutions compared to the STC only solution under constant total bile salt concentration and initial celecoxib concentration, although no lecithin was used in these studies.…”
Section: Compositions Of the Biorelevant Testing Mediasupporting
confidence: 93%
See 2 more Smart Citations
“…The significant difference between telaprevir induction times in FaSSIF and in the mixed micelles with lecithin solutions further demonstrates that STC may not be a good surrogate for human bile composition. Our results are in general agreement with those of Li et al 12 who reported a two fold increase in celecoxib induction time in mixed bile salt solutions compared to the STC only solution under constant total bile salt concentration and initial celecoxib concentration, although no lecithin was used in these studies.…”
Section: Compositions Of the Biorelevant Testing Mediasupporting
confidence: 93%
“…Most studies to date have focused on the crystallization inhibitory ability of individual bile salts. These studies revealed the potential of monomeric bile salts as nucleation [11][12][13] and/or crystal growth, 14 inhibitors. Furthermore, it was noted that bile salts showed a comparable inhibition ability to polymers for poorly water soluble drugs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The driving force for the common ion effect for weakly basic ionisable APIs is an increase in counterion concentration, which shifts the solubility equilibrium of the dissociated reaction to favour crystallization of the solid salt form of the API. The use of synthetic polymers, and recently of bile salts, to inhibit the crystallization of hydrophobic APIs is well described in the literature [3], [14]- [17], [21], [37], [38] This complements our previous study which shows how solution concentration and stability of CFZH + at pH 1.6 (in 25 mM HCl) depends on the presence and concentration of NaTc, lecithin, and pepsin in the system [22]. These results explain that the underlying mechanism for this manipulation of solution behaviour was through interference with the crystallization kinetics of CFZ hydrochloride from these solutions, with the exception of pepsin.…”
Section: Screening the Impact Of Polymers Bile Salts And Pepsin On Tmentioning
confidence: 99%
“…Most previous studies have focused on using polymeric additives, such as cellulose derivatives, to prolong supersaturation by inhibiting nucleation [14]- [17]. However, recently several studies have demonstrated that bile salts can also act as crystallization inhibitors for hydrophobic APIs [3], [18]- [21]. A recent systemic study of the effects of bile salts, phospholipids, and digestive peptides, on the solution concentration of the antibiotic agent clofazimine (CFZ), showed that the presence of these amphipathic compounds has a strong influence on solution behaviour i.e.…”
mentioning
confidence: 99%